Perencanaan Produksi Menggunakan Metode Algoritma Fuzzy Time Series Average – Based, Strategi Perencanaan Agregat dan Metode Transportasi - Sarah Julieta Simanjuntak; Drajat Indrajaya (LPPM, 2023)
Companies often have difficulty determining the right amount of production to meet demand. This is due to fluctuations in consumer demand from time to time. Production planning is related to the future, therefore production planning needs to be prepared on the basis of estimates made based on past data using several assumptions. The Fuzzy Time Series Average-Based Algorithm is a forecasting method with a fairly good level of accuracy because it implements an average system that is able to determine the length of the effective interval. In addition, it is important to determine the right strategy to minimize costs. This research produces forecasts for the next 1 year. The Mean Absolute Percentage Error (MAPE) value is 10.6% and the results are classified as Good. For the Aggregate Planning Strategy for tire products with a Level strategy, a fee of IDR 28,952,251,200 is obtained. While the Chase strategy costs Rp. 5,437,770,000 and for the Mixed strategy, a fee of Rp. 28,945,051,200. Then the alternative method of transportation for permanent workers results in a cost of Rp. 21,575,275,000 while the alternative workforce changed by Rp. 25,613,475,000. Then the calculation of the aggregate planning strategy using the Chase strategy method is the best method that can be used to meet production demands by minimizing production costs.Companies often have difficulty determining the right amount of production to meet demand. This is due to fluctuations in consumer demand from time to time. Production planning is related to the future, therefore production planning needs to be prepared on the basis of estimates made based on past data using several assumptions. The Fuzzy Time Series Average-Based Algorithm is a forecasting method with a fairly good level of accuracy because it implements an average system that is able to determine the length of the effective interval. In addition, it is important to determine the right strategy to minimize costs. This research produces forecasts for the next 1 year. The Mean Absolute Percentage Error (MAPE) value is 10.6% and the results are classified as Good. For the Aggregate Planning Strategy for tire products with a Level strategy, a fee of IDR 28,952,251,200 is obtained. While the Chase strategy costs Rp. 5,437,770,000 and for the Mixed strategy, a fee of Rp. 28,945,051,200. Then the alternative method of transportation for permanent workers results in a cost of Rp. 21,575,275,000 while the alternative workforce changed by Rp. 25,613,475,000. Then the calculation of the aggregate planning strategy using the Chase strategy method is the best method that can be used to meet production demands by minimizing production costs.